2008
DOI: 10.1002/mc.20492
|View full text |Cite
|
Sign up to set email alerts
|

c‐Fos accelerates hepatocyte conversion to a fibroblastoid phenotype through ERK‐mediated upregulation of paxillin‐Serine178 phosphorylation

Abstract: Transforming growth factor beta (TGF-beta) exerts an important role in the late steps of carcinogenesis by cooperating with Ras to induce cell motility and tumor invasion. The transcription complex AP-1 has been implicated in the regulation of genes involved in motility and invasion, by mechanisms not yet delineated. We utilized a model of immortalized human hepatocytes (IHH) overexpressing c-Fos (IHH-Fos) or not (IHH-C) to investigate the role of c-Fos on cell motility in response to a prolonged treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…As described in the Introduction, activation of the ERK signaling pathway requires the participation and mediation of PXN in prostate cancer and non-small cell lung cancer (10,17 (11). Several studies have demonstrated that Erk always gives a positive feedback on PXN and plays an important part in the activitation of PXN and interaction between FAK and PXN (11,22,23). Based on these facts, we decided to examine the expression of p-Erk during this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the Introduction, activation of the ERK signaling pathway requires the participation and mediation of PXN in prostate cancer and non-small cell lung cancer (10,17 (11). Several studies have demonstrated that Erk always gives a positive feedback on PXN and plays an important part in the activitation of PXN and interaction between FAK and PXN (11,22,23). Based on these facts, we decided to examine the expression of p-Erk during this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that c-Fos was highly expressed in cervical cancer, and almost never expressed in normal tissues and precancerous lesions ( 48 ). c-Fos expression was upregulated following TGF-β1 treatment in immortalized liver cells, which was correlated with cell migration and invasion ( 49 ). Therefore, we proposed that increased TGF-β1 promoted expression of c-Fos and the formation of heterodimers, and upregulated FUT1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Although paxillin is phosphorylated by active FAK [ 22 ], this study has revealed that paxillin expression is regulated by ERK1/2 and c-Jun activities. Activated ERK1/2 correlates with total paxillin expression and Ser178 phosphorylation but not with Tyr118 phosphorylation during EGF/TGFβ1-mediated hepatocyte migration [ 23 ]. The 3D culture using collagen I gels supplied with 10% FBS-containing culture media in this study efficiently showed laminin expression independent of KRS suppression, suggesting that laminin is available during the experiments in the 3D collagen I gels.…”
Section: Discussionmentioning
confidence: 99%